PEMBELAJARAN BERDIFERENSIASI PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Rika Nurbayanti; Herena Yanti Febriyanti; Sofyan Iskandar; Effy Mulyasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Differentiated learning is an instructional approach based on the understanding that each student has unique needs, interests, abilities, and learning styles. In the context of Civics Education (PKn), this implies that students come from diverse backgrounds, beliefs, and experiences, which can influence how they understand and apply the values of Pancasila and citizenship concepts in their daily lives. This study aims to analyze the effectiveness of differentiated learning in Civics Education for elementary school students. This research employs the Systematic Literature Review (SLR) method, utilizing the Publish or Perish (POP) tool with keywords such as